Put your ideas into words (Essex, UK, 1998)
Word Banks give help with writing essays on exam topics Innovative communication section provides essential words and phrases for spoken English 24-page Grammar Reference written by Professor David Crystal
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc